Journalism as a Channel for the Aspirations of the Community and Students of MA. Al-Arqom Sarirejo - Rofiqoh, Yusnia I’anatur; H, M. Lukmanul; A, Daghatsani F.; Susanto, Oaley M. Didin; Hadzafi , Ahmad Afaillah (Universitas Muhammadiyah Sidoarjo, 2024)
This study aims to explore the role of journalism as a channel for expressing aspirations within the environment of Madrasah Aliyah (MA) Al-Arqom Sarirejo, both for students and the surrounding community. In the era of information transparency, journalism functions not only as a medium for news dissemination but also as a participatory space for the public to voice their opinions, complaints, and hopes. Using a descriptive qualitative approach, data were collected through in-depth interviews, observations, and documentation. The results show that journalism activities at MA Al-Arqom serve as a constructive platform for expressing ideas and criticism in a polite and educational manner. Besides improving students’ media literacy, journalism activities also strengthen the relationship between the school and the community. The role of supervising teachers and active student involvement are key to the success of this journalism program. This study recommends strengthening journalism training and providing digital platforms as strategic steps to broaden the reach of public aspirations. Highlights: Journalism as a Voice – Empowers students and community to express opinions constructively. Media Literacy Growth – Enhances students' critical thinking and communication skills. School-Community Bond – Strengthens relationships through participatory media. Keywords: Journalism, Student Aspirations, Community Aspirations, MA Al-Arqom, Media Literacy, Educational Communication